How important is the impact of market timing on capital structure? A management perspective - Ibrahim, Khairunisah (s.n, 2013)
This study employs a survey approach in analytically identifying the presence as well as the importance of the market timing theory in explaining how Malaysian managers make their corporate financing decision. This study investigates whether the issuance decisions of firms are consistent with the traditional theories, notably the static trade- off and pecking order theories or the market timing behavior